Managing source of information and its relationship with fear of new strains of COVID-19 virus among a sample of Egyptians - Marwa Zein; Samar Anwar; Youssef Elsendiony; Alaa Qandeel; Marwa Salem (Microbes and Infectious Diseases, 2024)
Background: The COVID-19 pandemic has fueled a surge of misinformation, including about new variants like BA.2.86, raising concerns about its spread and the effectiveness of containment efforts. This "infodemic" has exacerbated the impact of the pandemic, leading to economic strain and psychological effects such as "coronophobia," with both traditional and social media playing significant roles in its propagation. Aim: to explore the level of fear of the new strains of COVID-19 among a sample of the Egyptian population and to identify the relationship between the level of fear and the technique of managing the information source. Methods: The current exploratory cross-sectional study was conducted among a sample from the general population using a pre-tested electronic questionnaire, which included the following sections: i) Sociodemographic characteristics, ii) fear of COVID-19 questions, and iii) Currency, Relevance, Authority, Accuracy, and Purpose (CRAAP) test to evaluate the source of information Results: About one third of the 390 participants were afraid of the new strains of COVID-19; thinking about that issue or watching news about it made them uncomfortable. The majority felt anxious or palpitated when they thought about getting one of the new strains of COVID-19. The mean score of fear of new strains of COVID-19was 15.9 ± 5.2. More than one third of them (32.1%) agreed that they always check the accuracy of the information by finding out if the information is supported by evidence or not. The fear of new strains of COVID-19 was significantly higher among females, married participants, and those suffering from chronic diseases. Conclusion: A significant proportion of the participants are not particularly afraid of new strains of viruses. About one third of them agreed that they always check the accuracy of the information by finding out if the information is supported by evidence or not.